2018
DOI: 10.12938/bmfh.18-006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Bacillus subtilis</i> C-3102 on bone mineral density in healthy postmenopausal Japanese women: a randomized, placebo-controlled, double-blind clinical trial

Abstract: Gut microbiota influence the host immune system and are associated with various diseases. In recent years, postmenopausal bone loss has been suggested to be related to gut microbiota. In the present study, we investigated the treatment effect of the probiotic Bacillus subtilis C-3102 (C-3102) on bone mineral density (BMD) and its influence on gut microbiota in healthy postmenopausal Japanese women. Seventy-six healthy postmenopausal Japanese women were treated with a placebo or C-3102 spore-containing tablets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 32 publications
(33 reference statements)
2
105
0
Order By: Relevance
“…Among them is the enhanced production of antimicrobial peptides by intestinal mac-31). Accordingly, individuals following a vegan or vegetarian diet, or those on a Mediterranean diet, have higher levels of SCFAs (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), and studies have indicated that these diets are beneficial to bone health (46,47).…”
Section: Sources and Mechanisms Of Scfa Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them is the enhanced production of antimicrobial peptides by intestinal mac-31). Accordingly, individuals following a vegan or vegetarian diet, or those on a Mediterranean diet, have higher levels of SCFAs (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), and studies have indicated that these diets are beneficial to bone health (46,47).…”
Section: Sources and Mechanisms Of Scfa Productionmentioning
confidence: 99%
“…Another trial with a multispecies probiotic showed a significant reduction in bone turnover, but no significant changes in BMD, perhaps because the trial duration was only 6 months (42). A 1-year-long trial in older women revealed evidence of a favorable change in bone mass in response to probiotic supplementation (43), and in a study in Japanese women, the probiotic Bacillus subtilis C-3102 increased total hip bone BMD by decreasing bone resorption (44).…”
Section: Modulation Of Gut-bone Axis By Probiotics and Prebioticsmentioning
confidence: 99%
“…Restoring a balanced gut microbiota is considered as a therapeutic tool for various diseases, including OP [ 695 , 730 , 731 , 732 , 733 , 734 , 735 , 736 , 737 ]. Recent studies showed that probiotic and prebiotic supplementation increases bone density in healthy individuals, protects against primary and secondary OP [ 687 , 695 , 699 , 734 , 738 , 739 , 740 ] and exerts beneficial effects in many other extra-digestive diseases [ 740 ]. However, despite the established impact of the gut microbiota on host (patho-) physiology, the potential roles of HPI- and medications-induced gut dysbiosis is not mentioned in current guidelines for OP.…”
Section: Clinical Implications and Recommendationsmentioning
confidence: 99%
“…The numbers of participants were similar and were divided randomly into the intervention group and the control group, among which seven studies were designed as double‐blind trials, and three studies were used cross‐control experiments. The studies met the inclusion were performed in six countries, including America (Holloway et al, ), Japan (Takimoto et al, ), Sweden (Nilsson, Sundh, Backhed, & Lorentzon, ), Taiwan (Tu et al, ), India (Gohel et al, ), and Iran (Asemi et al, ; Farhangi et al, ; Jafarnejad et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The values of baseline and end point of serum calcium level ( n = 5) and BMD ( n = 4) were reported in the majority of these trials. Two of the four studies reported BMD was included owing to T score report, and the other two studies were excluded from meta‐analysis because of the relative alteration of reported BMD between baseline and end point (Nilsson et al, ; Takimoto et al, ). Finally, six studies were preserved for meta‐analysis (Asemi et al, ; Farhangi et al, ; Gohel et al, ; Holloway et al, ; Jafarnejad et al, ; Tu et al, ).…”
Section: Resultsmentioning
confidence: 99%